Jawawawo Natural Monisms: Revelation Dimension of Peo and Inspiration for Faith-Dialogue in Multi Religious Society - Yakobus Ndona; Paulinus Tibo (Budapest International Research and Critics University, 2019)
Traditional faiths are still often regarded as animism, dynamism and superstition. The fact shows that traditional fatihs indicate various virtues and truth that can be inspiration for development of multi religious community existence today. The writer, from the result of research toward artefact metaphysic dimension in Jawawawo customary commuity, Central Keo, Indoneia, found out the form of natural monism religiousity which derives from genuine revelationexperience. Peo manifests vision of divinity in traditional faith of Jawawawo community, namely that is transcendent as well as immanent, absolute at once covers and underlies everything, far unlimted, at once involves in history and human life.This divine image shows that traditional faith of this community cannot be categorized as animism, dynamism and superstition; on the contrary, it gives inspiration for self development and faith-dialogue in multi religious community at present.